Unraveling the Link between Obesity and Tuberculosis: A Systematic Review of the Underlying Mechanisms - Deddy Herman; Rizanda Machmud; Nur Indrawaty Lipoeto (HM Publisher, 2025)
Background: Tuberculosis (TB) and obesity are significant global health concerns with potentially complex interactions. Obesity, through its effects on metabolism, inflammation, and the immune system, may influence TB susceptibility, progression, and treatment outcomes. This systematic review aims to analyze the published literature on the relationship between obesity and TB, focusing on the underlying mechanisms. Methods: A systematic search of PubMed, Science Direct, and Google Scholar was conducted for articles published in the last 10 years. The search strategy included keywords such as